Prateka Sawa Dengan Upacara Ngaben Kanista Pada Masa Pandemi Covid-19 di Kelurahan Abianbase Kecamatan Mengwi Kabupaten Badung - I Wayan Sujana (Jurnal Penelitian Agama Hindu, 2022)
One element of the aspect ceremonial that has recently received attention in religious activities is the ceremony prateka sawa at the ceremony ngaben kanista during the covid-19 pandemic period in Abianbase Village, Mengwi District, Badung Regency. In the current situation, according to government regulations through the relevant health office, if a person dies from the corona virus, the body is immediately handled by Covid-19 officers and taken to the crematorium. Because it is dangerous and can be contagious. Usually, public hospitals in Badung Regency are brought to the Santa Yana creatorium on Jalan Ahmad Yani Peguyangan or directly taken to the Bebalang Bangli Crematorium. The background of theritual prateka sawa during the covid-19 pandemic not only based on bhisama as the most important reason but also strengthened by socio-religious, cultural and economic reasons. This is accompanied by adaptations to strengthen the achievement of goals, strengthen integration and social control in the form of not daring to violate because of being cursed. Theritual system prateka sawa ritual for the diversity of Hindus in Abianbase Village continues with cremation related to the system religious, meaning that there are components such as beliefs, religious emotions, ritual systems, ritual equipment from religious people. These components synergize in a series of processes so as to give birth to the separation of the unification of the spirit into the sublime world with the mention of Dewa Hyang. The ritual of prateka sawa performed by the abianbase community has implications for variations on the abianbase community.